AHMAD IBN MUHAMMAD QUDURI'S CONTRIBUTION TO THE DEVELOPMENT OF HANAFI FIQH (Conferencea, 2023)
This article talks about the biographies, scientific works, opinions of Hamasr and later scholars about him, teachers and students of Abul Husayn Ahmad ibn Muhammad Quduri, the author of "Mukhtasarul Quduri", one of the royal works of the Hanafi school .